Method of Creating a Passive Optical Network Monitoring System - Токар, Л. О.; Krasnozheniuk, Y. (My University, 2021)
It is considered that with the simultaneous operation of two or more wireless users, which differ in speed performance, the phenomena of air monopolization appear, which is reflected in the imperfection of the built-in mechanisms of the IEEE 802.11 standard and the distribution of air time. The influence of the Airtime Fairness technology on the performance and quality of the Wi-Fi wireless network of the IEEE 802.11ac standard is investigated. The features of implementing of algorithms for the operation of the Airtime Fairness technology are considered, and the theoretical substantiation of the efficiency of this technology is presented. Statistical data were obtained aimed at optimizing the process of data transmission over the air. The collection and analysis of network performance indicators was carried out when activating the Airtime Fairness mechanisms with the preservation of all preliminary settings, equipment locations, locations of wireless users and their number. An analysis of the main indicators of the performance and quality of the wireless network is presented: the average traffic speed, packet performance and the number of TCP packets with loss or damage or re-transmitted to the network. It was revealed that the performance indicators of the network during the operation of the Airtime Fairness technology can vary depending on the equipment manufacturer and the technology operating mechanisms used by the manufacturer. It has been proven that the use of Airtime Fairness technology is advisable, but only with a full understanding of the performance mechanisms and features together with a clear understanding of the impact of this technology on the network and on each individual user.
Keywords: Monitoring; Passive Optical Network